The relevance of Islamic pillars of sustainable development in promoting shared prosperity / Nor Hazila Ismail and Mohamed Eskandar Shah Mohd Rasid - Ismail, Nor Hazila; Mohd Rasid, Mohamed Eskandar Shah (2017)
The extreme inequality in the distribution of wealth, income and opportunity undermines and distorts the sharing of prosperity, democracy, economic health and vitality, ecological balance, physical health and culture of the nations. The concept of sustainable development made an international breakthrough when the Report of the United Nations' World Commission on Environment and Development (WECD) was published in 1987. Interestingly, the approach of the Contemporary Sustainable Development is largely in consonance with the maqasid or objectives of the Shari'ah. Islam is a universal religion and addresses the entire mankind not the believers alone. It is, therefore, no surprise that people irrespective of faith do often think along Islamic lines. This research paper is a conceptual study in attempt to stipulate the notions for the future empirical research. Specifically, this study suggested the dimension of the Islamic pillars of sustainable development (both social and economic) on the poorest two quintiles of the population by evaluating the relationship between the factors and the changes in the per capita income of the poor in the developed and developing countries. It is hoped that this preliminary study helps in the determination of the Islamic pillars to sustainable development and significantly able to serve as an effective mechanism for poverty eradication in the respective countries.